Exploring the challenges of public private partnership on infrastructure projects in Ghana A case study at Takoradi Harbour Expansion Project - Kumordzie, Winfred (2021)
A thesis submitted to the Department of Construction Technology and Management, Kwame Nkrumah University of Science and Technology College of Art and Built Environment in partial fulfillment of the requirement for the Degree of